Bienvenida modernidad: revistas en La Araucanía y la construcción de la hegemonía (2013)
This article offers an analysis of the editorials that appeared in magazines published in the Araucanía region, in southern Chile, between 1912 and 1938.  Using a methodology based on discourse analysis, the authors show the magazines played a key role in instituting modernity in a historical context marked by interculturality.